Exporting Congress? : the influence of the U.S. Congress on world legislatures - Power, Timothy J. (Timothy Joseph), 1962-; Rae, Nicol C. (Pittsburgh, Pa. : University of Pittsburgh Press, 2006)
Trata da influência do Congresso americano no processo legislativo da Inglaterra, Canadá, America Latina, Alemanha e Letste Europeu.
Legislative diffusion : can the U.S. Congress be a source? / Timothy J. Power and Nicol C. Rae -- Reinstitutionalizing the British House of Commons : how relevant is the congressional model? / Nicol C. Rae -- So close, and yet so far : congressional influences on Canadian legislatures / Louis Massicotte -- Recorded voting and accountability in the United States and Latin American legislatures / John M. Carey -- Limits on exporting the U.S. Congress model to Latin America / Scott Morgenstern -- The influence of U.S. Congressional hearings on committee procedure in the German Bundestag / Gerhard Loewenberg -- The U.S. Congress's modest influence on the legislatures of Central and Eastern Europe / John R. Hibbing and Samuel C. Patterson -- The environmental determinants of legislative structure : a comparison of the U.S. House of Representatives and the European Parliament / Amie Kreppel -- Ballot structures and legislative behavior : changing role orientations via electoral reform / Pippa Norris -- Barriers and carriers : legislative diffusion and the selective imitation of Congress / Timothy J. Power and Nicol C. Rae.
Includes bibliographical references (pages 209-226) and index.
JSTOR
Keywords: United States. -- Congress; United States. -- Congress; Legislative bodies -- Case studies; Comparative government; Comparative government; Legislative bodies; Case studies